2002
DOI: 10.33584/jnzg.2002.64.2462
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenesis from forages fed to sheep

Abstract: Methane production has been measured from lambs fed contrasting forages. This work has been driven by the need to reduce greenhouse gas emissions from agriculture and to determine energy losses to methane from contrasting diets. Young ram lambs were fed either fresh ryegrass/white clover pasture, lucerne (also pelleted lucerne), sulla, chicory, red clover, Lotus pedunculatus (lotus) and mixtures of sulla and lucerne, sulla and chicory and chicory with red clover. The effects of condensed tannin (CT) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(101 citation statements)
references
References 8 publications
4
83
0
14
Order By: Relevance
“…In an earlier study, we showed that in vitro incubations with tamarind (Tamarindus indica) seed husk (containing approximately 140 g of CT/kg of DM), had lower gas production compared with incubations that had the added tannin-binder PEG (Bhatta et al, 2001). Waghorn et al (2002) reported that in vitro incubation of Lotus pedunculatus (containing tannin) had lower CH 4 production compared with L. pedunculatus treated with PEG. In the same study, sheep fed L. pedunculatus produced 17% less CH 4 compared with sheep fed L. pedunculatus plus PEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, we showed that in vitro incubations with tamarind (Tamarindus indica) seed husk (containing approximately 140 g of CT/kg of DM), had lower gas production compared with incubations that had the added tannin-binder PEG (Bhatta et al, 2001). Waghorn et al (2002) reported that in vitro incubation of Lotus pedunculatus (containing tannin) had lower CH 4 production compared with L. pedunculatus treated with PEG. In the same study, sheep fed L. pedunculatus produced 17% less CH 4 compared with sheep fed L. pedunculatus plus PEG.…”
Section: Discussionmentioning
confidence: 99%
“…Although tannins are generally regarded as antinutritional, certain tannins at low concentrations alter ruminal fermentation (Bhatta et al, 2002) and microbial protein synthesis (Bhatta et al, 2001). Tannins also reduce ruminal CH 4 production when included either as temperate legumes (Waghorn et al, 2002) or as purified tannin extracts (Roth et al, 2002). However, there are no reports on potential differences in the activities of HT and CT on CH 4 production and on methanogenic archaeal and ciliated protozoal populations.…”
Section: Introductionmentioning
confidence: 99%
“…A mĂȘme stade de vĂ©gĂ©tation, la teneur en NDF du sainfoin est plus faible, ou similaire Ă  celle de la luzerne (AufrĂšre et al 2008, Theodoridou et al 2011a. Une particularitĂ© des fourrages contenant des TC est leur richesse en glucides solubles (tableau 1) dont la teneur est beaucoup plus Ă©levĂ©e que celle des lĂ©gumineuses classiques (luzerne, trĂšfle) (Waghorn et al 2002, MinneĂ© et al 2002, ce qui favorise leur aptitude Ă  la conservation en ensilage.…”
Section: / Valeur Alimentaire Des LĂ©gumineuses Contenant Des Tannins unclassified
“…This is consistent with McMahon et al (1999), who reported that methane production was decreased linearly with increasing CT-containing forage (sainfoin; Onobrychis viccifoli; 11.3% CT) supplementation compared with nonCT-containing forage alfalfa (Medicago sativa). It has been reported in vivo that animals fed CT-containing forages reduced methane gas production in goats (Puchala et al, 2005), sheep (Waghorn et al, 2002), and dairy cows (Woodward et al, 2002). Evidence in support of the inhibitory effect of CT was provided by Tavendale et al (2005), who demonstrated that the accumulated methane production at 12 h incubation for Lotus pedunculatus (100 g of CT/kg of DM) was lower (8.8 vs. 12.5 mL) than alfalfa (2 g of CT/kg of DM).…”
Section: Condensed Tannins and Ruminal Gas Production Profilesmentioning
confidence: 99%